Livestock Farming in Cholistan Desert of Pakistan: Setting the Development Strategies - Farooq, Umar; Iqbal, Muhammad; Ahmad, Nunir (Annals of Arid Zone, 2016)
Identifying and developing the potential areas of livestock production in the country is part of the overall developmental strategy for this sector. Livestock in Cholistan represents a notable proportion of total animal population of Punjab province where livestock farming is primarily practiced under very difficult environment as no other livelihood opportunities prevail in the area. Herders with their animals keep moving from one toba to the other. It was found that due to lack of coordination, institutions of the area are working in isolation and much duplications in their work can be easily noticed. The average herd sizes are fairly large, mainly maintained to cover the diseases and drought risks. Besides this physical capital, low quantities of other capitals like human capital, natural capital and financial capital are present in the area. However, social capital is found to be quite strong. Other characteristics of the area are livestock production in isolation from amenities/necessities of life. Split grazing and natural breeding methods are observed in the area. Relatively more peculiar problems noticed include limited supply of forage and fodder, more physical exertion of animals while grazing, frequent incidence of diseases and drought, difficulties in getting health services and vaccination, least opportunities of getting children educated while moving from one toba to the other, poor health of the . animals, low milk productivity per animal, highly limited milk marketing opportunities, non-existence of milk preservation facilities with the herders leaves few options like early consumption of milk, feeding to young stock, and/or processing for making ghee and low prices of live animals received when sold. A number of short-term or high priority, as well as long-term or low priority areas are delineated for the researcher, development planners and policy makers for the overall development of livestock farming in the desert. Key words: Cholistan Desert, livestock farming, herders, milk products, grazing.